2018
DOI: 10.1016/j.heliyon.2018.e00816
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of corticosteroid in the treatment of dengue – A systemic review

Abstract: Corticosteroids are used therapeutically for a broad spectrum of diseases including autoimmune, allergic and inflammatory diseases. However in trials, the evidence for using corticosteroids in dengue is inconclusive and the quality of evidence is low. This systemic review is conducted to review clinical trials on dengue and steroid therapy to identify the current strength and weakness of evidence for the use of corticosteroids.We searched MEDLINE/PUBMED and Google scholar for publications on steroid use in den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…A recent systematic review showed that corticosteroids given to reduce the degree of inflammation in the period between CLS and DSS had a survival benefit[ 32 ] in dengue; however, there has been no study of their use in a subgroup of patients with ALF. One patient in our study received corticosteroids; unfortunately, she did not survive.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that corticosteroids given to reduce the degree of inflammation in the period between CLS and DSS had a survival benefit[ 32 ] in dengue; however, there has been no study of their use in a subgroup of patients with ALF. One patient in our study received corticosteroids; unfortunately, she did not survive.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence that immunosuppression does not worsen outcome comes from large scale trials in dengue, a related flavivirus. A comprehensive review that included 13 studies enrolling 1293 participants on the effectiveness of corticosteroids in the treatment of dengue, found no evidence that administration of high doses of oral or intravenous corticosteroids promoted viremia [180]. Rather, therapeutic benefit was seen in multiple studies that used intravenous delivery of high doses and multiple doses of steroids.…”
Section: Immunotherapeutic Interventionmentioning
confidence: 99%
“…The use of steroids is still controversial and not widely recommended, as several studies have shown that they do not affect clinical outcomes such as mortality. 33 The observed increased prescription of anti-inflammatories in patients with comorbidities (adjOR: 6.2, 95% CI: 1.5-24.5) may be due to the fact that most comorbidities were respiratory (3.3%) and rheumatological (1.5%), in which the use of anti-inflammatory drugs could be indicated, as is the case of exacerbated asthma or arthritis.…”
Section: Discussionmentioning
confidence: 99%